MENGONSTRUKSI PENDIDIKAN KRITIS HUMANIS DAN POPULIS; TINJAUAN TENTANG POLITIK PENDIDIKAN INDONESIA ERA GLOBALISASI INFORMASI (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2017)
In the era of global competition, every country tries to make real ecoÂnomic prosperity and science and technology advances that trigger ecoÂnomic change of the community that is more intellect, professional, and skilful in managing the nature and living environment for the purpose of fulfilling their needs. However, without being concerned, a decrease in quality of human personality has resulted also. Unsurprisingly, the free-market ideology and culture in various public domains have alienÂated education only as the vehicle of the capitalism's power used to humanize human beings. Consequently, education has experienced moral degradation and decadence, including orientation and vision switch. This article offers critical, humanist, populist education in a context of educational dynamics in Indonesia. Education, in the globalization era, like is being tested to give a dilemmatic answer, that is, between legitimizing and eventuating the existing social system and structure, or having critical roles in making social change and transformation into an equitable world. The both dilemmatic roles of education can only be answered through the selection process of its underlying educational paradigm and ideology.
Keywords: global competition; humanist; populist education